Investigation of chlamydophila abortus in abortion of cattle by pcr - Zeki Aras; Zafer Sayın; Gökçenur Sanioğlu Gölen (Eurasian Journal of Veterinary Sciences)
Aim: The purpose of this study was to investigate Chlamydophila abortus in fetal abomasal contents of cattle from Aksaray and Konya provinces by Polymerase Chain Reaction (PCR). Materials and Methods: A total of 65 fetal abomasal contents of cattle that were sent to Veterinary Diagnostic laboratories of Aksaray and Selçuk Üniversities from Aksaray and Konya provinces were used as sample. The occurrence of Chlamydophila abortus was investigated by PCR methods. Results: A total of 65 fetal abomasal contents of cattle were examined by PCR. Two (3%) fetal samples were found to be positive for C. abortus. In 63 (97%) samples, DNA of C. abortus were not detected and accepted to be negative. Conclusions: In this study, abortion cases due to C. abortus in cattle were showed in Aksaray, Konya region. In taken prevention, measures for bovine abortion cases in this region should be aware of C. abortus aetiology.